Comments on: “Early High-Titer Convalescent Plasma Therapy in Patients with Moderate and Severe COVID-19” [Transfusion and Apheresis Science 61 (2022) 103321] - Seyed Reza Hosseiniara (Journal of Preventive and Complementary Medicine)
Dear Editor We wish to draw attention to the recent study by Fazeli et al.,1 which investigates the efficacy of early high-titer convalescent plasma therapy in patients with moderate and severe COVID-19. The authors conclude that this therapy is beneficial for Iranian patients with moderate COVID-19 in the early stages of the disease. However, we have identified several critical limitations in the study design and findings that merit careful consideration when assessing the effectiveness of convalescent plasma therapy.A primary concern is the notably high mortality rate observed among the study participants. The investigation focused on patients with severe and moderate COVID-19 who received only convalescent plasma therapy, without any adjunct or standard treatment. Specifically, the mortality rates were reported as 13.7% for the moderate group and a staggering 86.3% for the severe group, culminating in an overall death rate of 29.7%.1 In contrast, a previous study by the same research group in 2020 reported a mortality rate of 24.3% in a control group that did not receive convalescent plasma but was treated with standard care.2 The similarities in the study settings for both investigations suggest that convalescent plasma therapy may have had no significant impact on mortality rates, potentially even contributing to higher mortality among Iranian patients.The lack of a control group receiving standard treatment in Fazeli et al.'s study1 significantly limits the ability to draw definitive conclusions regarding the efficacy of convalescent plasma therapy. Furthermore, a recent systematic review and meta-analysis encompassing 39 studies reported an overall pooled case fatality rate of 10% among COVID-19 patients.3 Other studies have indicated in-hospital mortality rates ranging from 4.5% to 8.8% among Iranian patients,4,5 while the mortality rate in intensive care units was found to be as high as 67.6%.6 Investigations conducted in other Asian populations have demonstrated mortality rates of 5-7.2% for patients with mild to moderate COVID-19.7,8 These findings are particularly relevant, as they suggest lower fatality rates than those observed in the study by Fazeli et al.,1 among Iranian patients treated with convalescent plasma therapy.Fazeli et al. conducted a multivariate logistic regression analysis to assess the effectiveness of high-titer convalescent plasma therapy in patients with moderate COVID-19. The analysis indicated a death rate of 6.9% when therapy was administered within five days of hospital admission, compared to 12.3% for those receiving treatment after five days.1 Consequently, the authors concluded that convalescent plasma therapy is beneficial for patients with moderate COVID-19 in the early stages of the disease.However, it is crucial to note that the authors did not account for the total length of hospital stay in their analysis, a factor that could significantly influence outcomes. Furthermore, it remains unclear whether patients who received high-titer convalescent plasma therapy later than five days post-admission had a similar length of hospital stay compared to those who began therapy earlier. It is plausible that patients receiving therapy later experienced longer hospital stays, which may have contributed to poorer outcomes, as previous research has shown a correlation between extended hospital stays and increased mortality risk in COVID-19 patients.9 Therefore, the authors' assertion regarding the efficacy of high-titer convalescent plasma therapy as a therapeutic option for patients with moderate COVID-19 during the early stages of the disease should be interpreted with caution.Additionally, the authors emphasize that "The use of COVID-19 convalescent plasma (CCP) has been approved by the Food and Drug Administration (FDA)." However, it is important to highlight that clinical trials adhering to the FDA's convalescent plasma treatment protocol have yielded concerning results. Specifically, 88% of patients experienced cardiac events, and 66% encountered thrombotic events while undergoing convalescent plasma treatment for COVID-19.10 Moreover, some studies reporting positive outcomes associated with convalescent plasma therapy did not utilize this treatment in isolation but rather as an adjunct to standard therapies.11Among studies that employed convalescent plasma therapy alone, Agarwal et al.,12 noted minor improvements in shortness of breath and fatigue; however, the evaluators were not blinded to subject data, which raises concerns about the reliability of their findings. Furthermore, while Maor et al.,13 suggested that convalescent plasma with higher antibody levels may benefit patients with moderate to severe COVID-19, this study did not report mortality outcomes and indicated that a longer follow-up period would be necessary to assess mortality rates adequately.It is also worth mentioning that convalescent plasma therapy is prohibited for COVID-19 patients in Iran,14 and the World Health Organization (WHO) has deemed this therapy ineffective.15 This body of evidence challenges the claims made by Fazeli et al.,1 regarding the efficacy of convalescent plasma therapy in treating Iranian patients with COVID-19.In conclusion, while Fazeli et al.'s findings contribute to the ongoing discourse on COVID-19 treatments, further rigorous studies are needed to validate the efficacy and safety of high-titer convalescent plasma therapy, particularly considering the limitations discussed herein.1One significant concern within the research community is the potential for conflicts of interest that may arise during the ethical approval process for investigations. In the present study, it is noteworthy that Dr. Eshghi, who chaired the ethics committee, is also listed as one of the corresponding authors of the article.16 Detailed information regarding Dr. Eshghi's role can be found in the "Credit Authorship Contribution Statement" section.1 This dual role raises important questions about potential conflicts of interest, which could lead to a biased review of the research proposal and ultimately undermine the credibility of the findings in the eyes of the public.Given these considerations, the assertion that convalescent plasma therapy is beneficial for Iranian patients with moderate COVID-19 is, at the very least, questionable. Future research should build upon the work of Fazeli et al.,1 considering the concerns we have raised. Until more robust evidence becomes available, we recommend that this critical topic remains open for further discussion.